Pygmy rabbit landscape genomics in the southern Great Basin - Byer, Nathan; Holding, Matthew; Crowell, Miranda; Pierson, Todd; Dilts, Thomas; Larrucea, Eveline; Shoemaker, Kevin; Matocq, Marjorie (Dryad, 2021)
Local adaptation can occur when spatially separated populations are
subjected to contrasting environmental conditions. Historically,
understanding the genetic basis of adaptation has been difficult, but
increased availability of genome-wide markers facilitates studies of local
adaptation in non-model organisms of conservation concern. The pygmy
rabbit (Brachylagus idahoensis) is an imperiled lagomorph that relies on
sagebrush for forage and cover. This reliance has led to widespread
population declines following reductions in the distribution of sagebrush,
leading to geographic separation between populations. In this study, we
used >20,000 single nucleotide polymorphisms (SNPs),
genotype-environment association methods, and demographic modeling to
examine neutral genetic variation and local adaptation in the pygmy rabbit
in Nevada and California. We identified 308 loci as outliers, many of
which had functional annotations related to metabolism of plant secondary
compounds. Likewise, patterns of spatial variation in outlier loci were
correlated with landscape and climatic variables including proximity to
streams, sagebrush cover, and precipitation. We found that populations in
the Mono Basin of California likely diverged from other Great Basin
populations during late Pleistocene climate oscillations, and that this
region is adaptively differentiated from other regions in the southern
Great Basin despite limited gene flow and low effective population size.
Our results demonstrate that peripherally isolated populations can
maintain adaptive divergence.
Keywords: FOS: Natural sciences